A Preliminary trial on the effect of an indigenous medicine in the management of Rheumatoid arthritis - R.Krishnakumar
Rheumatoid arthritis is a chronic symmetrical inflammatory poly arthritis which mainly affectsthe peripheral synovial joints, but is often associated with extra articular features. All the systems of medicine are facing difficulties in managing the disease and none of them could claim a complete mastery over the disease. In the present study, an attempt to find out an effective remedy for Rheumatoid arthritis was done. The bark of Bodhivruksha (Ficus religiosa Linn.) and seeds of Chandrasoora (Lepidium sativum Linn) which were found effective in the management of the disease in the previous mstudies were successfully combined with the help of a pharmaceutical modification process viz, Bhavana (medicinal impregnation) told in Ayurvedic classics. This combination was selected for the present study. The study design of the present study was randomised clinical trial. Fourty-five patients were selected according to the criteria. Selected patients were placed in three groups and were administered with the single drugs and the combined drug in appropriate dosage; for a period of 30 days. Assessments were done before and after the treatment. The results were analysed and found that the combination of the said single drugs, was statistically significant, and it was found superior in efficacy when compared with the individual usage of the single drugs.